Estudo da permeabilidade à água na camada de cobrimento de protótipos de concretos com altos teores de cinza volante - Petry, Simone Bassan (2004)
The civil construction industry is, as times goes by, more related with echo-social efficiency and society and the concrete, most used building material, has its use associated with concerns on the durability and the performance of the constructions, looking for the optimization of the natural resources. The durability esteem of a concrete is the function of impermeability of it, since the entrance of water and deleterious agents initiates the mechanism of deterioration of structure, with the reinforcement corrosion. The covercrete has an important function in the steel protection, acting as a first barrier to the entrance of these agents and, therefore, the concrete quality is related to the impermeability of this layer constituent. In order to analyze the capacity of carrying fluids to the interior of the part (in the reinforcement direction) through the superficial pores through water absorption and diffusivity of it analyzing the differences in the covercrete. This study intend to approach the laboratory assay with the structures of concrete in situ that s why it is realized in extracted speciements of the prisms cured in environmental conditions of the construction. High fly ash (50%) , are used in substitution of the cimenticious materials, with and without addition of lime in the concrete for a better performance in relation of the carbonatation and other variables. The study focus 0; 2,5 and 5,0cm deep to know the behavior of the studied proprieties in the covercrete.